(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the efficacy, safety, and sustainability of various advanced diagnostic tools and wearing-targeted therapies on patients clinical outcome of Chronic Rhinosinusitis With Nasal Polyps. Study Design: A prospective observational study. Place and Duration of Study: This study was conducted at the Department of ENT Khyber teaching hospital Peshawar from January 2021 to January 2023. Methods: This study was performed on 100 patients with Chronic Rhinosinusitis with Nasal Polyps, where advanced imaging, sinonasal endoscopy, and biomarker profiling were employed. It comprised of systemic corticosteroids, different surgeries and biological products. Symptom severity scores and radiological characteristics were used to assess clinical effectiveness. Qualitative comparison TMS efficacy Statistical analysis Self administered questionnaire Compared treatment efficacy Self administered questionnaire Compared treatment efficacy. Results: Among 100 patients (mean age: 42.(mean = 3 ± 12.8 years), biologics had enhanced symptoms as compared to standard treatments (p < 0.01). Imaging revealed at least a 50% reduction in lesion size in 82 percent of cases. On average, scores of patients’ symptoms increased by 45% after the treatment. The patients under treatment of simple remedies containing biologic products recorded fewer cases of relapses with quicker recuperation span. Conclusion: Newer diagnostic methods have enhanced our understanding and management of Chronic Rhinosinusitis with Nasal Polyps with available biologic agents. Methods founded on MRI targeted to the individuality of the patient improve outcomes and patient satisfaction: this is a new model of medicine.